Enhancing Maternal Understanding of Infant Immunization Through Intensive and Discovery-Based Approaches: A Quasi-Experimental Study - Kusmiati, Endang; Indawati, Eli (STIKep PPNI Jawa Barat, 2025)
Background: Children's health issues are one of the government's priorities in creating a quality generation. One effort to achieve this goal is that all children under five are given immunization. The challenge in implementing the immunization program which causes the immunization coverage target to not be achieved is the low level of knowledge. So the role of Health workers is to provide information using demonstration methods and discovery methods. Objectives : To determine the effectiveness of the demonstration method and discovery method on mothers' knowledge about the completeness of basic immunization for babies in the working area of the Cibadak District. Method: This research used quasi-experimental research with a sample size of 36 people. Data techniques include univariate analysis using frequency distribution and bivariate analysis using paired t test. Result: The results of this study show that there is an influence of health education methods and findings on maternal knowledge about the completeness of basic immunization, p value 0.000. Conclusions and Suggestions: Providing education using discovery is more effective than demonstration in increasing mothers' knowledge about basic immunization. It is hoped that the provision of education can be implemented to increase mothers' knowledge of basic immunization.